10.1016/S0271-7964(08)70054-5 (CrossRef Listing of Deleted DOIs, 2000)
PURPOSE: The growing prevalence of obesity, MetS, and T2DM highlights the need to better understand host-microbiota interactions. While gut microbiota has been widely investigated, interactions between the oral microbiota and human salivary proteins remain largely unexplored. EXPERIMENTAL DESIGN: This study investigated the integrated human salivary proteome and bacterial secreted metaproteome in Brazilian individuals spanning different metabolic states: normal weight/control, overweight, obesity, MetS, and T2DM. Saliva samples were analyzed using mass spectrometry-based proteomics to identify differential protein profiles. RESULTS: Key findings revealed significant downregulation of human proteins MYSM1 (eta2 = 0.710, 95% CI: [0.642, 0.825], qadj< 0.001) and GAD65 (η2 = 0.478, 95% CI: [0.368, 0.681], qadj < 0.001) in obese, MetS, and T2DM groups, correlating negatively with BMI, waist circumference, and HOMA-IR, suggesting impaired anti-inflammatory and endocrine functions that exacerbate metabolic dysregulation. Conversely, carbonic anhydrase VI (CA6) was markedly upregulated (η2 = 0.374, 95% CI: [0.274, 0.570], qadj < 0.001), showing positive correlations with systolic blood pressure and glucose levels, indicative of an acidic, inflammatory oral microenvironment linked to chronic low-grade inflammation. In the bacterial secreted metaproteome, TrxC-2 (η2 = 0.557, 95% CI: [0.501, 0.727], qadj < 0.001), UMPK (η2 = 0.629, 95% CI: [0.571, 0.781], qadj < 0.001), and RsmH (η2 = 0.772, 95% CI: [0.718, 0.862], qadj 0.001) were significantly elevated in obesity, MetS, and T2DM, positively associated with anthropometric and insulin resistance markers, reflecting microbial adaptations to oxidative stress and enhanced virulence through biofilm formation and RNA biosynthesis. Interactome analysis demonstrated strong negative correlations between bacterial proteins and human proteins (MYSM1, GAD65), alongside positive correlations with CA6, unveiling a vicious cycle, where oral dysbiosis amplifies host inflammation and metabolic dysfunction, while altered human proteins perpetuate microbial imbalance. CONCLUSIONS AND CLINICAL RELEVANCE: These findings underscore the pivotal role of host-microbiota interactions in the oral cavity during the pathogenesis of obesity, MetS, and T2DM, highlighting the importance of further elucidating the molecular and functional mechanisms underlying microbiota-host crosstalk in metabolic diseases.